INDIRECT WRITTEN CORRECTIVE FEEDBACK (WCF) IN TEACHING WRITING - Haris Budiana; Mahmud Mahmud (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2020)
Indirect Written Corrective Feedback (WCF) is a type of feedback on linguistic errors without giving the correct target form. This type of feedback is recommended under the consideration that teachers are not editors, but facilitators who provide hints to assist students work on their own text. This research investigated the students’ affective reactions toward indirect WCF in the process of learning writing. It was also purposed to investigate its impact on students’ writing quality. The subject of the research was the first-year students of English Study Program. The method of the research was descriptive qualitative. The instruments of interview and writing assignment were deployed as the data. It was found there were positive affective reactions toward the implementation of Indirect WCF. Students thought that it was useful, helpful, motivating, corrective, and informative. Nevertheless, a few students felt that the time given was too short and demanded for more accurate and clear correction codes. It was also found that Indirect WCF helped the participant students gain better quality of their paragraph writing indicated in the significant reducing number of errors after receiving feedback. Though the most types of linguistic errors were found in the case of tenses, students were able to minimize those errors into a few.